Resource Box for Resilient Seed Systems. On-line learning modules. - Vernooy, Ronnie; Besette, G.; Rudebjer, P.G.; Otieno, G. (Bioversity International, 2015)
The Resource Box for Resilient Seed Systems is a learning material based on Bioversity International’s long experience in seed systems research at local, national and global levels. It contains a methodology to build resilient seed systems that meet the needs of tomorrow and help farmers adapt to climate change effects.